Evolutionary Trajectories of Shoots vs. Roots: Plant Volatile Metabolomes Are Richer but Less Structurally Diverse Belowground in the Tropical Tree Genus Protium - Katherine D. Holmes; Paul V. A. Fine; Italo Mesones; Julieta Alvarez-Manjarrez; Andressa M. Venturini; Kabir G. Peay; Diego Salazar (Plants)
The breadth and depth of plant leaf metabolomes have been implicated in key interactions with plant enemies aboveground. In particular, divergence in plant species chemical composition—amongst neighbors, relatives, or both—is often suggested as a means of escape from insect herbivore enemies. Plants also experience strong pressure from enemies such as belowground pathogens; however, little work has been carried out to examine the evolutionary trajectories of species’ specialized chemistries in both roots and leaves. Here, we examine the GCMS detectable phytochemistry (for simplicity, hereafter referred to as specialized volatile metabolites) of the tropical tree genus Protium, testing the hypothesis that phenotypic divergence will be weaker belowground compared to aboveground due to more limited dispersal by enemies. We found that, after controlling for differences in chemical richness, roots expressed less structurally diverse compounds than leaves, despite having higher numbers of specialized volatile metabolites, and that species’ phylogenetic distance was only positively correlated with compound structural distance in roots, not leaves. Taken together, our results suggest that root specialized volatile metabolites exhibit significantly less phenotypic divergence than leaf specialized metabolites and may be under relaxed selection pressure from enemies belowground.